Lung Transplantation Using a Hybrid Extracorporeal Membrane Oxygenation Circuit. Issue 10 (November 2020) - Thomas, Mathew; Martin, Archer K.; Allen, Wesley L.; Makey, Ian A.; Renew, J. Ross; Rodrigues, Eduardo S.; Mordecai, Monica M.; Brown, Thomas E; Foeks, Jeremy J.; Johnson, James L.; Landolfo, Kevin L.; Pham, Si M.
Abstract : Extracorporeal circulation (ECC) support using intraoperative extracorporeal membrane oxygenation (ECMO) during lung transplantation (LTx) is now a routine practice for many high volume centers. Circuits that are dedicated to ECMO alone can be expensive and do not allow full cardiopulmonary bypass (CPB) to be performed. We describe our technique of instituting venoarterial ECMO during LTx using a less-expensive hybrid circuit that facilitates easy and immediate conversion to full CPB if needed, without interruption of ECC.